Genetic technology and the evolution of property rights: The case of decode Genetics - Thráinn Eggertson (University of Iceland, Institute of Economic Studies (IoES), 2008)
Recent advances in biology and genetics have raised the value of life samples, health records and genetically modified micro-organisms, and, as Demsetz (1967) predicts, rising values increase the demand for well-defined exclusive ownership rights. But greater expected value of resources also fires up various claimants who compete in political, judicial and ideological domains to advance their interests. I illustrate the complex evolution of property rights in modern biotechnology (and in other fields) by analyzing the well-known case of Decode Genetics, a for-profit research firm that tried to collect all of Iceland's health records into a central electronic database. Decode Genetics fought two rounds with the informal owners of the health records—the country's medical establishment. The first round focused on formal institutions. In the second round, which involved informal institutions, the insiders managed to block the national databank project. Yet, the firm became renowned for its research into the genetic causes of major diseases. The paper shows that Decode Genetics was able to carry on by switching to a new game plan. Under the new strategy the firm relies on Coasean bargaining to acquire necessary genetic material and health records.
Keywords: 330; property law; genetic engineering; database; healthcare; data protection; Coase's theorem; Iceland; Sachenrecht; Gentechnik; Datenbank; Gesundheitswesen; Datenschutz; Coase-Theorem; Island